Genome-Wide Association Study of Seed Folate Content in Common Bean - Martin, C. Joe; Torkamaneh, Davoud; Arif, Muhammad; Pauls, Karl Peter (Frontiers in Plant Science, 2021)
Plant-derived folates (Vitamin B9) are essential components of the human diet. They provide one-carbon units that are required for the synthesis of nucleic acids and proteins, and folate deficiency is associated with numerous adverse health conditions. The development of high-folate cultivars of common bean (P. vulgaris) and other staple crops is an important tool to combat folate deficiency. A population of 100 P. vulgaris accessions, representing major North American market classes, was grown in two years in Ontario, Canada. The population was genotyped for 5361 molecular markers with an Illumina Infinium platform. Total folate was extracted from mature seeds using the tri-enzyme extraction method and quantified based on a microbiological assay with Lactobacillus rhamnosus. Significant genetic diversity for folate content was observed among the population in both years of study, and folate content had a range 113-222 micrograms per 100 grams of seeds. Quantitative trait loci (QTL) for seed folate content were identified based on an analysis of variance and a genome-wide association study (GWAS). Six QTL were identified on Chr. 4, 6, 8, and 11, with three in each year of field trials. Both QTL on Chr. 11 occurred in genomic regions that were syntenic to seed folate QTL detected in previous work with P. vulgaris, Z. mays, and O. sativa. Candidate genes were identified for these QTL, including an S-adenosyl-L-methionine-dependent methyltransferase gene, a uridine diphosphate-dependent glucosyltransferase gene, a gene encoding an HXXXD-type acyl-transferase family protein, and a SECRETORY PROTEIN 14 (SEC14)-like gene. This work reports the largest survey of genetic diversity for seed folate content in P. vulgaris and identified several genotypes, including SCN4, Bat 93, OAC Redstar, and Pompadour 1014, that would be useful for breeding beans with higher than average folate levels.